P0198SODIUM ZIRCONIUM CYCLOSILICATE INCREASES SERUM BICARBONATE CONCENTRATIONS AMONG PATIENTS WITH HYPERKALAEMIA: RESULTS FROM THREE RANDOMIZED, MULTI-DOSE, PLACEBO CONTROLLED TRIALS. (6th June 2020) - Roger, S; Spinowitz, Bruce; Lerma, Edgar; Fishbane, Steven; Ash, Stephen; Martins, Julian; Moreno Quinn, Carol; Packham, David
Abstract: Background and Aims: Sodium zirconium cyclosilicate (SZC; formerly ZS-9) is an orally-administered, non-absorbable, inorganic, selective potassium (K + ) binder for the treatment of adults with hyperkalaemia. SZC entraps K + throughout the gastrointestinal tract in exchange for hydrogen and sodium ions. In addition to serum K + reduction, phase 2 clinical trial data have shown an increase in serum bicarbonate and a decrease in serum urea. This may be due to SZC trapping of ammonium ions (which are of a similar size to K + ions) in the gastrointestinal tract. Maintaining serum bicarbonate ≥22 mmol/L preserves kidney function and reduces metabolic bone disease. Thus, SZC-induced increase in serum bicarbonate may represent an effect of clinical significance. We present a post hoc analysis of central laboratory-measured serum bicarbonate, urea, and urine pH data from three randomized, placebo-controlled, phase 3 studies of SZC among patients with hyperkalaemia (ZS-003, HARMONIZE, and HARMONIZE-Global). Method: In all studies, patients initially received up to 10 g SZC three times a day (TID) for 48 hours for correction of hyperkalaemia (randomized placebo-controlled in ZS-003, open-label in HARMONIZE and HARMONIZE-Global), followed by randomization to maintenance therapy with SZC up to 15 g once a day (QD) versus placebo for up to 29 days among those who achieved normokalaemia during the correction phase. Results: The analysis included 753 patients from the initial 48-hour correction phase of ZS-003, and 208 and 214 patients who completed the 29-day maintenance phase of HARMONIZE and HARMONIZE-Global, respectively. Significant dose-dependent increases from baseline in serum bicarbonate of 0.3–1.5 mmol/L occurred within 48 hours of SZC TID in ZS-003 (Figure A), which occurred regardless of chronic kidney disease (CKD) stage (Figure B). Similar acute increases in HARMONIZE and HARMONIZE-Global were maintained over 29 days with SZC ≥10 g (Figure C) and ≥5 g QD (Figure D), respectively. Mixed-model least-squares mean serum bicarbonate increases from baseline versus placebo over 15–29 weeks with SZC were 2.2 mmol/L (p <0.001) and 2.8 mmol/L (p <0.001) in HARMONIZE (SZC 15 g QD) and HARMONIZE-Global (SZC 10 g QD), respectively. In ZS-003, the proportion of patients with serum bicarbonate <22 mmol/L at correction phase baseline, 27.3%, fell to 16.5% (p = 0.025) at 48 hours among patients receiving SZC 10 g TID. In HARMONIZE and HARMONIZE-Global, the proportion of patients with serum bicarbonate <22 mmol/L at correction phase baseline, 39.4% and 87.9%, respectively, fell to 4.9% (p = 0.005) and 70.1% (p = 0.006) at 29 days, respectively, among patients receiving the highest SZC maintenance dose (15 g and 10 g, respectively). Parallel decreases in serum urea and increases in urine pH were also observed with SZC in all three studies. Mixed-model least-squares mean serum urea decreases from baseline versus placebo over 15–29 weeks with SZC were −1.0 mmol/L (p = 0.029) and −2.9 mmol/L (p <0.001) in HARMONIZE (SZC 15 g QD) and HARMONIZE-Global (SZC 10 g QD), respectively. Corresponding increases in urine pH were 0.23 (p = 0.001) and 0.35 (p <0.001), respectively. Path analysis demonstrated that changes in serum urea (but not changes in serum potassium or urine pH) were associated with the SZC effect on serum bicarbonate. Conclusion: SZC consistently and dose-dependently increases serum bicarbonate concentrations, reduces the proportions of patients with serum bicarbonate <22 mmol/L, decreases serum urea, and increases urine pH during treatment of hyperkalaemia. These changes in serum bicarbonate occur regardless of CKD stage and are sustained during ongoing maintenance therapy. The increase in serum bicarbonate is associated with change in serum urea rather than with changes in serum K + or urine pH, supporting the hypothesis that SZC traps ammonia in the gastrointestinal tract independently to its effect on K + binding.